Analysis of the Implementation of the Cold Work Permit System on the DHU Unit of the Absorber Column at PT Z - Anugrah, Rezky; Dona P. H, Adinda; Fatih H, Muhammad; Sadrina D, Nur (Sahabat Publikasi, 2024)
This research analyzes the implementation of the Cold Work Permit system in the Dehydration Unit (DHU) of the absorber column at PT Z. This system aims to ensure work safety in high-risk activities, such as maintenance and cleaning that are associated with exposure to harmful gases, noise, and potential ergonomic hazards. These risks can be minimized through the implementation of the Safe Work Permit (SIKA) which serves as a risk control document and a medium for coordination between linked parties. This research uses a descriptive qualitative approach with field observation, interviews, and document analysis. The results of the research show that the cold work permit system at PT Z has been implemented quite well. Maintenance work such as replacement and cleaning of stack arresters in DHU units complies with occupational safety standards that link the measurement of hazardous gases, such as H?S, CH? and oxygen. The permissible gas content is within safe limits, which is a minimum oxygen content of 19.5%, an optimal H?S of 1 ppm, and CH? at a LEL value of 0%. However, carbon monoxide (CO) measurements have not been carried out entirely, which could increase the risk of harm to workers. Inadequate monitoring of CO can pose a risk of poisoning, shortness of breath, and even death if the concentration exceeds 25 ppm. The positive impact of the implementation of this system is an increase in work safety and a reduction in the risk of accidents in the DHU unit. However, the research also found that additional training is needed to improve workers' understanding of the importance of CO gas monitoring and the prevention of ergonomic hazards. An increase in work procedures through the improvement of SIKA documents and more intensive coordination between linked parties is also recommended